Substance Abuse and Rural Appalachian Pediatric Trauma in West Virginia. (26th June 2022) - Rawson, Joshua; Thevenin, Lindsey; Balko, Isabella; Seifarth, Federico; Meltzer, Hal; Dhumak, Vipul; Bush, Amy; Kimble, Wesley; Wen, Sijin; Ellison, Pavithra
Abstract : Introduction . Rural Appalachia is endemic to issues such as substance abuse, poverty, and lack of community support, all of which negatively influence health outcomes. The incidence of pediatric trauma as it relates to substance abuse is of concern in the region, where the rate of positive drug screens in pediatric trauma cases is higher than national average. Methods . The West Virginia statewide pediatric trauma database was analyzed in a retrospective cohort study for the years 2009-2019. Variables of interest included injury severity (assessed using Abbreviated Injury Scale (AIS)), drug screening results, and various measures of patient outcome. Results . The sample was divided into 2009-2016 presentations (n = 3, 356 ) and 2017-2019 presentations (n = 1, 182 ). Incidence of critical (AIS 5) head injuries (p = 0.007 ) and serious (AIS 3) neck injuries (p = 0.001 ) increased as time progressed. Days requiring ventilation increased from 3.1 in 2009–2016 to 6.3 in 2017–2019 (p < 0.001 ). Drug screens were obtained at a rate of 6.9% in 2009–2016 versus 23.3% in 2017–2019 (p < 0.001 ). Benzodiazepine use increased from 0.8% to 1.8% (p < 0.001 ), and opioid use increased from 1% to 4.9% (p < 0.001 ). Conclusion . The increasing severity of pediatric trauma and substance abuse in Appalachia is of significant concern. The use of respiratory drive-depressing drugs has risen, just as the severity of head and neck traumas has increased. These results emphasize the importance of targeted interventions in the rural pediatric population.